Genetic variation of high-altitude Ecuadorian population using autosomal STR markers. Issue 1 (December 2019) - Zambrano, A.K.; Gaviria, A.; Vela, M.; Rodríguez-Pollit, C.; Guevara-Ramírez, P.; López-Cortés, A.; Armendáriz-Castillo, I.; García-Cárdenas, J.M.; Guerrero, S.; Leone, P.E.; Pérez-Villa, A.; Yumiceba, V.; et al.
Abstract: Fifteen autosomal STRs were analyze in order to elucidate the differences between low and high land Ecuadorian population. Seven Ecuadorian geographic areas (Tisaleo-Mocha, Cañar, Quito, Rocafuerte, Santa Rosa, Guayaquil and Lago Agrio) from different altitude were selected for the study. After the analysis, little genetic distances were observed between all cities, the more distant cities (FST  = 0.02354) were Rocafuerte at an elevation of 17 m.a.s.l. and Quito at 2850 m.a.s.l. and the similar cities (FST  = 0.00033) were Rocafuerte (17 m.a.s.l.) and Santa Rosa (10 m.a.s.l). In conclusion, there is not a great genetic distance in the 15 STRs reported in high and low land Ecuadorian population, therefore previously reported frequencies could been used in identification and paternity cases under analysis.